Prediction of U.S. daily mask wearing and social distancing using psychologically valid agents during three waves of COVID-19 - Teng, Choh Man; Pirolli, Peter; Bhatia, Archna; Carley, Kathleen; Dorr, Bonnie; Lebiere, Christian; Mather, Brodie; Mitsopoulos, Konstantinos; Morrison, Don; Orr, Mark; Strzalkowski, Tomek (Frontiers in Epidemiology, 2025)
We present Regional Psychologically Valid Agents (R-PVAs) as a modeling approach to predicting transmission-reducing behaviors and epidemiology. The approach builds upon computational cognitive theory and formalizes aspects of theories of individual-level behavior change. We present R-PVA models of social distancing and mask wearing in response to dynamics in the physical and information environments in the 50 U.S. states. The models achieve strong goodness-of-fits for predicting day-to-day mask-wearing (R2 = 0.93) and social distancing (R2 = 0.62) for the first three waves of COVID-19, prior to the rollout of vaccines.